High-frequency sectoral carbon and environmental analysis based on monthly input-output tables compilation during 2018–2021 - Duo Xu; Gengyuan Liu; Hui Li; Fanxin Meng; Yu Chen; Feni Agostinho; Cecilia M.V.B. Almeida; Biagio F. Giannetti (iScience, 2023)
Summary: This paper proposes a process for updating monthly input-output tables with monthly macroeconomic statistics and published input-output tables. Reasonable assumptions are set up and 48 monthly input-output tables are prepared from 2018 to 2021 with the combination of the row range series method and nonlinear mathematical planning. The Weaver-Thomas composite index is used to analyze the role of the sector in the economic network, and the sectoral correlation indicators are used to analyze the correlation change of the sector’s monthly electricity emissions to show an environmental application effect of the monthly input-output table. The results show that the monthly input-output tables can be prepared with acceptable accuracy, and they can reveal the sectoral network structure changes and sectoral carbon emissions changes in continuous monthly time series. The proposed approach contributes for the compilation of high-time-frequency input-output tables, so as to support high-frequency industrial environmental impact analysis.